Frequency and progression of azotemia during acute and chronic treatment of congestive heart failure in cats - Sarah Rogg; Jonathan P. Mochel; Debosmita Kundu; Melissa A. Tropf; Allison K. Masters; Darcy B. Adin; Jessica L. Ward (Journal of Veterinary Internal Medicine)
Abstract Background Azotemia is common in cats with congestive heart failure (CHF) and might be exacerbated by diuretic therapy. Hypothesis/Objectives Determine frequency, risk factors, and survival impact of progressive azotemia in cats treated for CHF. Animals One hundred and sixteen client‐owned cats with kidney function testing performed at least twice during acute or chronic CHF treatment. Methods Serum creatinine (sCr) and electrolyte concentrations were determined at multiple clinical timepoints to detect azotemia and kidney injury (KI; sCr increase ≥0.3 mg/dL). Furosemide dosage between timepoints was calculated. Multivariable modeling was performed to identify predictors of KI, change in serum biochemistry results, and survival. Results Azotemia was common at all timepoints, including initial CHF diagnosis (44%). Kidney injury was documented in 66% of cats. Use of a furosemide continuous rate infusion was associated with increased risk of KI during hospitalization (odds ratio, 141.6; 95% confidence interval [CI], 12.1‐6233; P = .01). Higher furosemide dosage was associated with increase in sCr during hospitalization (P = .03) and at first reevaluation (P = .01). Treatment with an angiotensin converting enzyme inhibitor was associated with fewer lifetime KI events (P = .02). Age in years was the only variable associated with shorter survival (hazard ratio, 1.1; 95% CI, 1.0‐1.1; P = .03). Neither sCr nor KI were associated with long‐term outcome. Conclusions and Clinical Importance Azotemia and KI were common in cats during CHF treatment but did not impact survival.